Women, gender and power among indigenous peoples of Portuguese Timor - da Silva, Kelly Cristiane (Anuário Antropológico, 2018)
This essay examines the social position of women and the implications of gender representations among indigenous peoples in post-World War II Portuguese Timor. It is a bibliographic critique based on works of academic anthropology and of certain missionary and colonial administrative ethnographies published between the 1950s and 1980s. I argue that in general women occupied a relatively subaltern position in the collective dynamics of social reproduction. This results from the specificity of local social structures and from the separation of sex and gender. I attempt to elucidate an apparent contradiction: on the one hand, femaleness, as a gender classifying principle, is associated with superiority among many peoples in Timor-Leste and, on the other hand, women are often in subaltern positions regarding collective reproduction. I argue that the ways the female principle and the idea of fertility are ritually handled serve the purpose of producing and reproducing male dominance in the dynamics of collective social reproduction and the co-opting of women’s power of giving life.